Empirical prediction of peak pressure levels in anthropogenic impulsive noise. Part I: Airgun arrays signals - Galindo Romero, M.; Lippert, T.; Gavrilov, Alexander (2015)
This paper presents an empirical linear equation to predict peak pressure level of anthropogenic impulsive signals based on its correlation with the sound exposure level. The regression coefficients are shown to be weakly dependent on the environmental characteristics but governed by the source type and parameters. The equation can be applied to values of the sound exposure level predicted with a numerical model, which provides a significant improvement in the prediction of the peak pressure level. Part I presents the analysis for airgun arrays signals, and Part II considers the application of the empirical equation to offshore impact piling noise.